Treatment of pediatric convulsive status epilepticus - Becker, Lena-Luise; Gratopp, Alexander; Prager, Christine; Elger, Christian E.; Kaindl, Angela M. (Frontiers in Neurology, 2023)
Status epilepticus is one of the most common life-threatening neurological emergencies in childhood with the highest incidence in the first 5 years of life and high mortality and morbidity rates. Although it is known that a delayed treatment and a prolonged seizure can cause permanent brain damage, there is evidence that current treatments may be delayed and the medication doses administered are insufficient. Here, we summarize current knowledge on treatment of convulsive status epilepticus in childhood and propose a treatment algorithm. We performed a structured literature search via PubMed and ClinicalTrails.org and identified 35 prospective and retrospective studies on children <18 years comparing two and more treatment options for status epilepticus. The studies were divided into the commonly used treatment phases. As a first-line treatment, benzodiazepines buccal/rectal/intramuscular/intravenous are recommended. For status epilepticus treated with benzodiazepine refractory, no superiority of fosphenytoin, levetirazetam, or phenobarbital was identified. There is limited data on third-line treatments for refractory status epilepticus lasting >30 min. Our proposed treatment algorithm, especially for children with SE, is for in and out-of-hospital onset aids to promote the establishment and distribution of guidelines to address the treatment delay aggressively and to reduce putative permanent neuronal damage. Further studies are needed to evaluate if these algorithms decrease long-term damage and how to treat refractory status epilepticus lasting >30 min.